Changing commercial policy in Japan during 1985 - 2010 - Masahiro Kawai; Shujiro Urata (Asian Development Bank Institute (ADBI), 2010)
In this paper we examine the changing nature of Japan's commercial policy over the last 25 years while reviewing Japan's changing structure of trade, FDI and economy that underlay policy changes. We argue that until the late 1990s Japan adopted a two-track approach of relying on multilateral liberalization under the GATT/WTO and open regionalism under Asia-Pacific Economic Cooperation (APEC) on the one hand and on the bilateral trade relationship with the US on the other. Although the Japan-US bilateralism sometimes resulted in managed trade and encountered negative perceptions of the US approach in Japan, overall, it had a positive impact on the Japanese economy in opening domestic markets through various reforms and deregulation measures. Japan's more recent commercial policy focuses on bilateral and plurilateral economic partnership agreements particularly with - but not limited to - East Asian economies. We argue that agricultural sector liberalization is key to the further integration of Japan with the Asian and global economies.
Keywords: F13; F14; F50; 330; Außenwirtschaftspolitik; Handelsregionalismus; Außenhandelsstruktur; Direktinvestition; Japan